A Diagnostic and Policy Options for the Vocational Education and Training System in Belarus - World Bank (World Bank, Washington, DC, 2021)
This report contributes to the scarce literature on labor market outcomes of different levels of education and returns to education in Belarus. Previous calculations of returns to education in Belarus were carried out for 1996-2001 (Pastore and Verashchagina 2006) and for 1995-2011 (Chubrik 2013). Unlike previous studies that emphasized higher education, this analysis concentrates on returns to VET. The report shows patterns of returns to education that are consistent with previous studies for Belarus and recent estimates for Russia (Melianova and others 2020). The results from Russia are particularly relevant given the institutional similarities between Russia and Belarus. The report is structured as follows. Section two presents an overview of education and the VET system, along with recent macroeconomic, education and labor market trends in Belarus. Section three describes the data and methodology used for the analysis. Section four provides the main results of the World Bank’s analysis of the labor market outcomes of VET graduates compared to graduates of other educational programs. It also includes analysis of the socioeconomic status of VET compared to general education students. Finally, section five offers policy recommendations for the improvement of VET system in Belarus while section six concludes the report with concluding remarks.